2022
DOI: 10.3389/fsurg.2022.918198
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Lymph Node Staging Systems in Gastric Adenocarcinoma after Neoadjuvant Therapy – A Population-Based Study

Abstract: IntroductionNeoadjuvant treatment leads in a reduction in positive lymph nodes and examined lymph nodes (ELN), which may affect assessment of lymph node staging and postoperative treatment. We aimed to compare the staging systems of lymph node ratio (LNR), the positive logarithm ratio of lymph nodes (LODDS), negative lymph nodes (NLN), and the 8th AJCC ypN stage for patients with gastric adenocarcinoma after neoadjuvant therapy.Materials and MethodsData was collected from the Surveillance, Epidemiology, and En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In our study, we showed that the LNR was a more appropriate LN system for assessing patient prognosis. Despite similar findings reported in prior studies (53)(54)(55)(56)(57)(58)(59), some of which also utilized data from the SEER database (54,58), our study possesses some distinct characteristics that differentiate it from earlier research. We collected SEER data from 2010 to 2020.…”
Section: Discussionmentioning
confidence: 59%
“…In our study, we showed that the LNR was a more appropriate LN system for assessing patient prognosis. Despite similar findings reported in prior studies (53)(54)(55)(56)(57)(58)(59), some of which also utilized data from the SEER database (54,58), our study possesses some distinct characteristics that differentiate it from earlier research. We collected SEER data from 2010 to 2020.…”
Section: Discussionmentioning
confidence: 59%
“…[25][26][27] This finding has significant implications, particularly for patients receiving NAC. 28 However, NAC can destroy the anatomic dissection plane, which makes LN dissection challenging. 7,29 Moreover, chemotherapy-induced fibrotic tissue changes influence lymphatic drainage, which may affect the efficacy of carbon nanoparticles (another commonly used tracer).…”
Section: Discussionmentioning
confidence: 99%
“…Thorough lymphadenectomy increases the number of LN dissections and prevents missed dissections of metastatic LNs, which is associated with accurate staging, treatment optimization, and improved prognosis 25–27 . This finding has significant implications, particularly for patients receiving NAC 28 . However, NAC can destroy the anatomic dissection plane, which makes LN dissection challenging 7,29 .…”
Section: Discussionmentioning
confidence: 99%